Description Behavior Care Self (Self Care) Sufferer Hypertension at the Health Center Kutalimbaru Deli Serdang Regency 2022 - Agustaria Ginting; Murni Sari Dewi Simanullang; Novia Kristin Surbakti (Institute of Computer Science (IOCS), 2022)
Hypertension is a non-communicable disease characterized by an increase in blood pressure from normal limits. Complications of hypertension can be prevented by doing good self care . Self care is an action taken independently to improve health, prevent disease and maintain health. Self care for people with hypertension can be done by applying 5 components, namely self-integration, self-regulation, interaction with health workers and others, blood pressure monitoring, and adherence to recommended rules. The purpose of the study was to determine the description of self-care behavior of patients with hypertension at the Kutalimbaru Health Center , Deli Serdang Regency in 2022. Methods Descriptive research design with cross sectional design. The population is 456 people, the research sample is 124 people. The sampling technique used purposive sampling. Data collection was selected directly using a questionnaire. The results based on self-integration are good at 65.3%, self-regulation is good at 74.2%, Interaction with health workers and others is good at 54.0%, poor blood pressure monitoring is 87.9%, Compliance with the rules recommended good at 87.1%. on blood pressure monitoring, it was found that hypertension patients have bad behavior in routinely monitoring their blood pressure, it is hoped that the health workers of the Kutalimbaru Health Center can provide education and health education regarding good self-care behavior in controlling blood pressure routinely once a month for hypertensive patients .